Konstruksi Sosial dan Ekonomi Tataniaga Beras: Fenomenologi Tataniaga Beras Dari Kabupaten Demak ke Kota Semarang - Margaretha Astri Viona; Darwanto Darwanto (MEDIA, 2014)
This study aimed to analyze the distribution of rice from Demak to Semarang. Analysis of distribution and profit relationship contained prices, costs and benefits of each of distribution agencies. This study used qualitative analysis. Primary data were obtained from an informant interviews with snowball sampling method. Furthermore, the data processed by adopting Miles and Huberman analysis model, which consisted of three stages: data reduction, display / presentation of data and verification / conclusions. Results of this research were the rice trade system was not only seen economically, but it could be seen from the social side. From the social side, rice trading system was the result of social construction processes who involved in rice trading system from Demak district to Semarang city. The highest margin trading system was in the longest line that was 62.96 percent. There were transaction costs of the cost component in the line of rice trading system. Transaction costs in this study were the costs incurred by traders and milling grain to seek information and negotiate or bargain in the purchase of grain.